Unmanned aerial vehicles (UAV) in the structures of the prison service in Poland - Rafał Parczewski; Anna Borucka; Grzegorz Kaliciak; Mirosław Radwan (Journal of Modern Science, 2023)
Objectives The main research objective was to examine the suitability of the BSP system to ensure effective support for penitentiary units in the performance of daily business tasks. The main research problem was formulated in the form of a question: What functionalities of the UAV system are useful for the tasks performed by SW? The main research hypothesis took the form of an assumption that the functionalities possessed by UAVs can provide significant support in the performance of tasks by PS officers and constitute an element of their development that should be implemented. The collected material of the researchers was used to formulate proving conclusions on the suitability of unmanned systems for official tasks performed by the Prison Service.